Loneliness and Mental Health in Response to Early and Late COVID-19 Outbreak: A Cross-Sectional Study of Czech Adults Aged 50 and Over - Vaculíková, Jitka; Hanková, Magdalena (Gerontology & geriatric medicine, 2023)
The unpredictable spread of the COVID-19 pandemic, national lockdowns, and public health measures implemented in the Czech Republic had a negative effect on older adults' mental health and loneliness. The 2,631 older adults in 2020 and 2,083 older adults in 2021 used in this study formed a nationally representative sample of the Survey of Health, Ageing and Retirement in Europe (SHARE). Almost every third older adult experienced feelings of loneliness in both stages of the COVID-19 outbreak. Loneliness increased in 2021 in those individuals who reported their physical health as poor, who felt nervous, sad or depressed, and who had ever left their home since the outbreak. According to age-related drivers of loneliness, feelings of loneliness were prevalent (40% vs. 45%) among younger retirees in both waves. In both data sets, declared feelings of sadness or depression were the strongest sustainable predictor of loneliness (2020 and 2021 models, OR = 3.69; 95% CI [2.90, 4.69] and OR = 2.55; [1.97, 3.30]). Being a woman and feeling nervous equated with a higher likelihood of feeling lonely compared to counterparts. Policy makers should therefore aim to carefully improve psychosocial and health-related consequences faced by this vulnerable population during the pandemic and beyond.
Keywords: loneliness; mental health; SHARE study; COVID-19